Pyonephrosis Associated with Massive Nephrolithiasis and Spontaneous Steinstrasse Managed by Open Nephroureterectomy: A Case Report - Chandra Sie, Jemmy; Dahril, Dahril (Journal of Neonatal Surgery, 2026)
Introduction: Pyonephrosis is a urological emergency caused by suppurative infection of an obstructed renal collecting system, most commonly due to urolithiasis. Steinstrasse is typically encountered as a complication following extracorporeal shock wave lithotripsy, whereas spontaneous steinstrasse in the absence of prior intervention is exceedingly rare. Its coexistence with massive nephrolithiasis and pyonephrosis represents an unusual and challenging clinical scenario. Case Presentation: We report a rare case of pyonephrosis secondary to an obstructing renal pelvic stone, associated with multiple nephrolithiasis and spontaneous steinstrasse. The patient presented with chronic flank pain and was found on imaging to have extensive stone burden involving the kidney and a continuous chain of calculi along the ureter. Despite preserved laboratory parameters, radiological findings suggested a chronically obstructed and infected, non-functioning renal unit. Considering the severity of infection and extensive ureteral involvement, a double-incision open nephroureterectomy was performed. Intraoperatively, more than 50 calculi were removed from the kidney and ureter. The postoperative course was uneventful, and follow-up imaging demonstrated complete stone clearance. Conclusion: Pyonephrosis associated with massive nephrolithiasis and spontaneous steinstrasse is extremely rare and potentially life-threatening. In the presence of severe infection and a non-functioning kidney, open nephroureterectomy offers definitive source control. This case underscores the continued relevance of open surgery in selected complex urolithiasis cases despite advances in minimally invasive techniques.